2020
DOI: 10.3389/fcell.2020.563607
|View full text |Cite
|
Sign up to set email alerts
|

Cytomegalovirus Generates Assembly Compartment in the Early Phase of Infection by Perturbation of Host-Cell Factors Recruitment at the Early Endosome/Endosomal Recycling Compartment/Trans-Golgi Interface

Abstract: Beta-herpesviruses develop a unique structure within the infected cell known as an assembly compartment (AC). This structure, as large as the nucleus, is composed of host-cell-derived membranous elements. The biogenesis of the AC and its contribution to the final stages of beta-herpesvirus assembly are still unclear. In this study, we performed a spatial and temporal analysis of the AC in cells infected with murine CMV (MCMV), a member of the beta-herpesvirus family, using a panel of markers that characterize … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
94
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(100 citation statements)
references
References 94 publications
(197 reference statements)
6
94
0
Order By: Relevance
“…Our previous study demonstrated the accumulation of Arf (Arf1–6) proteins at the AC in the late phase of MCMV infection (at 48 hpi) [ 6 ]. Thus, we first analyzed the expression level and intracellular recruitment of all Arf proteins in the early phase of infection at the pre-AC stage.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Our previous study demonstrated the accumulation of Arf (Arf1–6) proteins at the AC in the late phase of MCMV infection (at 48 hpi) [ 6 ]. Thus, we first analyzed the expression level and intracellular recruitment of all Arf proteins in the early phase of infection at the pre-AC stage.…”
Section: Resultsmentioning
confidence: 99%
“…These data indicate that class I Arf proteins are rapidly upregulated in MCMV-infected cells, which can be a consequence of either increased synthesis or slowed degradation. The rapidity of upregulation together with the analysis of the host cell transcriptome, which demonstrated no significant alteration in any of the mRNAs of the Arf proteins in the early phase of infection [ 6 ], suggest that observed increases of the levels of Arf proteins are more likely due to altered mechanisms controlling endogenous class I Arf protein degradation rather than a consequence of altered synthesis.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations